Kajian Tampungan Kapasitas Hulu Bendung Karet Tirtonadi pada Penanganan Banjir Kota Surakarta Paket – 3 - Sugiarta, Anton; Solikin, Mochamad; Harnaeni, Senja Rum (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2023)
ABSTRACT: The rainy season of river water discharge / times often experiences an increase in the capacity of water volume derived from the intensity of rainwater. This often has the impact of damage to the right and left of the river flow / times and sediment buildup at several locations through which it passes. The study was conducted to find out the upstream capacity of tirtonadi rubber weir after the implementation of the flood management of Surakarta Package – 3 based on the parameters of physical condition assessment and simulation with HEC-RAS 5.0.3 software. Primary data collection by requesting images of work or as built drawing for long sections and cross sections directly to the contractor while to obtain secondary data about river conditions, rainfall, water level and AWLR data of Bengawan Solo River obtained from data from BBWS Bengawan Solo and data from BPSDA Bengawan Solo. The design debit calculation method uses the Nakayasu HSS method. And the results of the Q50 calculation in the results of simulations conducted with HEC-RAS 5.0.  The results of the analysis show that the maximum flood discharge of Kali Pepe obtained from rainfall on December 15, 2020, it is known that the discharge capacity of the Kali Pepe Q50th river is 998.39 m3/s. Adding the capacity of the upstream Kali Pepe river to 673.39 m3/s from the capacity of the old upstream Kali Pepe river of 325 m3/s. And the storage capacity after implementing package-3 Surakarta city flood handling resulted in a volume of 710,870 m3 Keywords : Flood discharge, HSS Nakayasu, HEC-RAS, Pepe River, Analysis, River capacity, storage capacity